Up-regulation of caveolin 1 mediated by chitosan activates Wnt/ β-catenin pathway in chronic refractory wound diabetic rat model. Issue 1 (1st January 2022) - Gao, Jie; Zhang, Jiayuan; Xia, Lianheng; Liang, Xuewei; Ding, Wukun; Song, Meiyu; Li, Linggen; Jia, Zhen
ABSTRACT: Diabetes mellitus (DM) can be implicated in the perturbations of vascular integrity and the dysfunction of angiogenesis. Chitosan has the advantage of promoting the vascular endothelial cell proliferation. However, the molecular mechanism of action in the promotion of wound healing by chitosan derivatives is still debated. In the current study, DM with chronic wound (CW) model rats were prepared and treated with chitosan. Vascular endothelial cells isolated from granulation tissues were conducted by RNA sequencing. Two thousand three hundred and sixteen genes were up-regulated, while 1, 864 genes were down-regulated after chitosan treatment compared to CW group. Here, we observed that caveolin 1 (CAV1) was highly expressed induced by chitosan. Furthermore, we observed that CAV1 knockdown could compromise the activation of Wnt pathway by reduction of β-catenin in rat aortic endothelial cells (RAOECs) and brain endothelium four cells (RBE4s). Moreover, we determined a direct interaction between CAV1 and β-catenin by IP assay. The C-terminus of CAV1 and β-catenin (24 to 586 amino acids) contributed to the interaction of these two proteins. Finally, the protein docking analysis indicated that the fragments of β-catenin (253–261 'FYAITTLHN' and 292–303 'KFLAITTDCLQI') might have affected the structure by CAV1 and facilitated the resistance to degradation. Taken together, our study demonstrates that chitosan can up-regulate CAV1 expression, and CAV1 can interact with β-catenin for promotion of canonical Wnt signaling pathway activity. Our results deepens the molecular mechanism of the Wnt pathway in vascular endothelial cells and is beneficial to developing new targets to assist in enhancing the pharmacological effect of chitosan on wound healing and angiogenesis against DM.